Generation of a human induced pluripotent stem cell line overexpressing CCL22 with islet cells differentiation potential - Duan Jinliang; Bai Fang; Zhu Xiaofeng; He Xiaoshun; Hu Anbin (Stem Cell Research, 2024)
CCL22 is a macrophage-derived immunosuppressive chemokine that recruits regulatory T cells through the CCL22:CCR4 axis, playing an important role in homeostatic and inflammatory responses. A CCL22-overexpressing human induced pluripotent stem cell line (CNNDi001-A-2) was generated by lentiviral transduction to further study the function of CCL22. The cell line was confirmed to have normal proliferation and pluripotency and could be further differentiated into islet cells for cell replacement therapy in diabetes.